Documents on modern history of economic thought Pt. C. - Glaeser, Martin G.; Samuels, Warren J., 1933-; Smith, Victor E.; Jaffé, William (Emerald, 2003)
This work contains seven documents from the history of economics: Four sets of lecture notes taken by Victor E. Smith, two from courses given by William Jaffe at Northwestern University, on general equilibrium theory and on Keynes, from 1938-39, and one from lectures given at the University of Cambridge during 1954-55. It includes two documents from the history of Institutional Economics, one the 1974 Editor's Report on the Journal of Economic Issues - on the conflicts then rampant - and the other, an exposition of the past and future of Institutional Economics, both by Warren J. Samuels. It also includes a set of autobiographical notes by the Wisconsin institutionalist, Martin G. Glaeser, and a bibliography of the writings of F.Y. Edgeworth by Alberto Baccini.
Keywords: Economics -- Study and teaching (Higher); Economics -- Methodology.; Economics -- Research.; elektronické knihy; electronic books